Soybean C2H2-Type Zinc Finger Protein GmZFP3 with Conserved QALGGH Motif Negatively Regulates Drought Responses in Transgenic Arabidopsis - Zhang, Dayong; Tong, Jinfeng; Xu, Zhaolong; Wei, Peipei; Xu, Ling; Wan, Qun; Huang, Yihong; He, Xiaolan; Yang, Jiayin; Shao, Hongbo; Ma, Hongxiang (Frontiers in Plant Science, 2016)
Plant response to environmental stresses is regulated by a complicated network of regulatory and functional genes. In this study, we isolated the putative stress-associated gene GmZFP3 (a C2H2-type Zinc finger protein gene) based on the previous finding that it was one of two genes located in the QTL region between the Satt590 and Satt567 markers related to soybean tolerance to drought. Temporal and spatial expression analysis using quantitative real-time PCR indicated that GmZFP3 was primarily expressed in roots, stems and leaf organs and was expressed at low levels in flowers and soybean pods. Moreover, GmZFP3 expression increased in response to polyethylene glycol (PEG) and Abscisic acid (ABA) treatments. In addition, subcellular localization analysis indicated that GmZFP3 was ubiquitously distributed in plant cells. Transgenic experiments indicated that GmZFP3 played a negative role in plant tolerance to drought. Analysis of ABA-related marker gene expression in Arabidopsis suggested that GmZFP3 might be involved in the ABA-dependent pathway during the drought stress response. Taken together, these results suggest that soybean GmZFP3 negatively regulates the drought response.